Evaluasi Strategis Pengelolaan MGMP Bahasa Sunda dalam Meningkatkan Kinerja Guru SMA Negeri di Kota Tasikmalaya - Kamilasari Kamilasari; Enas Enas; Asep Budi Tauhid (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the strategic management evaluation of the Sundanese Language Subject Teacher Forum (MGMP) in improving teacher performance at public senior high schools in Tasikmalaya City. The study focuses on leadership management, member participation, institutional support, and program relevance to teachers’ professional development needs. This research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving MGMP administrators, member teachers, school principals, and supervisors. Data analysis used the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The findings revealed that the MGMP management has generally functioned effectively as a professional learning community. Participatory leadership patterns encouraged collaboration among teachers in designing learning tools and solving classroom problems. However, several challenges were identified, including inconsistent program evaluation, limited technological integration, unequal member participation, and insufficient funding support. The study also found that MGMP programs significantly contributed to improving teachers’ pedagogical competence, especially in lesson planning and instructional implementation. Nevertheless, assessment and evaluation competencies still require further strengthening. This study concludes that strategic management, sustainable evaluation, and institutional support are essential in optimizing MGMP functions to improve teacher performance and the quality of Sundanese language learning.